2007
DOI: 10.1063/1.2785151
|View full text |Cite
|
Sign up to set email alerts
|

Spectral characterization of transparent (Nd0.01Y0.94La0.05)2O3 laser ceramics

Abstract: The spectrum properties of transparent (Nd0.01Y0.94La0.05)2O3 ceramics were investigated. It was found that all absorption bands of (Nd0.01Y0.94La0.05)2O3 ceramics are broadened, of which the full width at half maximum of the peak centered at 804nm is 8nm and its absorption cross section is 1.02×10−20cm2. The emission cross section of (Nd0.01Y0.94La0.05)2O3 ceramics located at 1078nm is 5.71×10−20cm2 and its fluorescent lifetime is 0.214ms, which are similar to those of 1.0at.%Nd:Y2O3 ceramics. These indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…[14] The intensity of Raman bands decreases, which means the symmetry of the crystalline structure is lowered, and similar results have also been reported in Eu 3+ -doped Y 2 O 3 [15] and Yb 3+ -doped Y 2 O 3 [16,17] compounds. Compared to the La 2 O 3 -undoped specimen, it is apparent that each band of (Nd 0.01 La x Y 0.99−x ) 2 O 3 (x = 0.05, 0.10) suffers a red shift due to the weak bond strength of La-O and heavy mass of La 3+ ion, as a consequence of which the phonon energy is slightly reduced.…”
Section: Resultssupporting
confidence: 69%
“…[14] The intensity of Raman bands decreases, which means the symmetry of the crystalline structure is lowered, and similar results have also been reported in Eu 3+ -doped Y 2 O 3 [15] and Yb 3+ -doped Y 2 O 3 [16,17] compounds. Compared to the La 2 O 3 -undoped specimen, it is apparent that each band of (Nd 0.01 La x Y 0.99−x ) 2 O 3 (x = 0.05, 0.10) suffers a red shift due to the weak bond strength of La-O and heavy mass of La 3+ ion, as a consequence of which the phonon energy is slightly reduced.…”
Section: Resultssupporting
confidence: 69%
“…Compared with Nd:Y 2 O 3 , it is also found that its absorption peak bands are broadened, especially in the LD wavelength 806 nm, of which the absorption coefficient is about 9 cm −1 , and the full width at half-maximum is about 8 nm, which is two times that of Nd:Y 2 O 3 ceramics (4 nm), four to seven times that of Nd 3+ :YAG ceramics [9]. It may be induced by a disorder occupation of the sites of Nd 3+ in the Nd:(Y 0.9 La 0.1 ) 2 O 3 transparent ceramics [5]. As the radius of Nd 3+ (98 pm) [10] has the similar size to those of La 3+ , it can substitute both the lattice sites of La 3+ (103 pm) and Y 3+ (89 pm) ions.…”
Section: Resultsmentioning
confidence: 95%
“…We can see the letters under the samples clearly. It was reported that (Y 1−x La x ) 2 O 3 transparent ceramics exit in the stable form of bixbyite, same to that of Y 2 O 3 , which make it possible to get a high transparency [5,6].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…E-mail addresses: xmao@siom.ac.cn (X. Mao), lzhang@siom.ac.cn (L. Zhang). matrix of solid solution of La 2 O 3 /Y 2 O 3 had large absorption cross section and emission cross section than those of Y 2 O 3 because of cubic glass-like structure [14], which were liable to achieve the miniaturized LD pumping apparatus and ultra-short mode-locked pulse laser output, respectively [15].…”
Section: Introductionmentioning
confidence: 99%